THE CRUCIAL ROLE DIPLOMATIC RELATIONS ON CONFLICT MANAGEMENT IN AFRICA - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Third-party interventions into ongoing civil wars are complex attempts to manipulate the preferences of warring parties, and thus conflict outcomes. These attempts to alter the course of a conflict can include providing materiel, intelligence, and money to change the structure of the relationship among combatants, or alternatively, providing information through mediation and other diplomatic initiatives to change the information that they hold about their adversary. Both approaches can have conflict management goals, although mediation has a much more direct link to a goal of containing violence and making peace. Conceptually, however, the two approaches to intervention could work in unison.